El Constructivismo : un marco teórico problemático - Sebastià, José M. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
Constructivism is one of the fundamental theoretical frameworks that has been orientating the research in science education over the last years. In this article several characteristics of the theory are underlined, and several aspects based on empirical evidence are collected and critically discussed.